Clinical efficacy of collagenase Clostridium histolyticum in the treatment of Peyronie's disease by subgroup: results from two large, double‐blind, randomized, placebo‐controlled, phase III studies. (18th May 2015) - Lipshultz, Larry I.; Goldstein, Irwin; Seftel, Allen D.; Kaufman, Gregory J.; Smith, Ted M.; Tursi, James P.; Burnett, Arthur L.
<x xml:space="preserve">Abstract</x> Objectives To examine the efficacy of intralesional collagenase Clostridium histolyticum (CCH) in defined subgroups of patients with Peyronie's disease (PD). Patients and Methods The efficacy of CCH compared with placebo, assessed from baseline to week 52, was examined in subgroups of participants from the Investigation for Maximal Peyronie's Reduction Efficacy and Safety Studies (IMPRESS) I and II. The subgroups were defined according to: severity of penile curvature deformity at baseline (30–60° [n = 492] and 61–90° [n = 120]); PD duration (1 to ≤2 [n = 201], >2 to ≤4 [n = 212] and >4 years [n = 199]); degree of plaque calcification (no calcification [n = 447], non‐contiguous stippling [n = 103] and contiguous calcification that did not interfere with injection of CCH [n = 62]); and baseline erectile function (International Index of Erectile Function [IIEF] scores 1–5 [n = 22], 6–16 [n = 106] and ≥17 [n = 480]). Results Reductions in penile curvature deformity and PD symptom bother were observed in all subgroups. Penile curvature deformity reductions were significantly greater with CCH than with placebo for the following subgroups: baseline penile curvature 30–60° and 61–90°; disease duration >2 to ≤4 years and >4 years; no calcification; and IIEF score ≥17 (high IIEF‐erectile function score; P < 0.05 for all). PD symptom bother reductions were significantly greater in the CCH group for: penile curvature 30–60°; disease duration >4 years; no calcification; and IIEF score 1–5 (no sexual activity) and ≥17 (P < 0.05 for all). Conclusions In this analysis, clinical efficacy of CCH treatment for reducing penile curvature deformity and PD symptom bother was found across subgroups. In the IMPRESS I and II overall, adverse events (AEs) were typically mild or moderate, although treatment‐related serious AEs, including corporal rupture or penile haematoma, occurred. Future studies could be considered to directly assess the efficacy and safety of CCH treatment in defined subgroups of PD patients, with the goal of identifying predictors of optimum treatment success.